2019
DOI: 10.1016/j.seizure.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Underutilization of epilepsy surgery in ASEAN countries

Abstract: This survey was performed to determine the availability of epilepsy surgery, and understand the limiting factors to epilepsy surgery in ASEAN countries with total of 640 million population. Method: A cross-sectional survey was completed by national representatives in all ASEAN countries (Brunei,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Consequently, there regions that were not represented (Africa, Latin America, and Southeast Asia), commensurate with areas where SEEG was currently not routinely practiced. 33 Data curation was required for pulse width where units were inaccurately reported or a range was provided, and removed for cases where input was seemingly unreasonable. The conservative approach to data management may have resulted in charge density being slightly underestimated.…”
Section: Limitationsmentioning
confidence: 99%
“…Consequently, there regions that were not represented (Africa, Latin America, and Southeast Asia), commensurate with areas where SEEG was currently not routinely practiced. 33 Data curation was required for pulse width where units were inaccurately reported or a range was provided, and removed for cases where input was seemingly unreasonable. The conservative approach to data management may have resulted in charge density being slightly underestimated.…”
Section: Limitationsmentioning
confidence: 99%
“…10 In the 11 countries (Indonesia, Philippines, Vietnam, Thailand, Myanmar, Malaysia, Cambodia, Laos, Singapore, East Timor, and Brunei) of the Association of Southeast Asian Nations (ASEAN), there were 42 epilepsy centers serving 640 million people in 2018. 11 Korea had 14 centers for 48 million people. 11 Although the years of the data were different, China and Korea had approximately the same per capita number of epilepsy centers, which was higher than that of ASEAN countries and lower than that of the United States.…”
Section: F I G U R Ementioning
confidence: 99%
“…11 Korea had 14 centers for 48 million people. 11 Although the years of the data were different, China and Korea had approximately the same per capita number of epilepsy centers, which was higher than that of ASEAN countries and lower than that of the United States.…”
Section: F I G U R Ementioning
confidence: 99%
“…8 A recent cross-sectional survey study in ASEAN countries showed that epilepsy surgery is severely underutilized, and concluded that lack of expertise, epilepsy centers, and funding contribute to this underutilization. 9 Due to the lack of reports on the utilization and outcome of epilepsy surgery, especially in pediatric patients in the Eastern Mediterranean Region, this retrospective study examines the outcomes of resective surgery in pediatric patients with DRE.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the favorable outcome, epilepsy surgery is still underutilized globally, including in the developed nations 8 . A recent cross‐sectional survey study in ASEAN countries showed that epilepsy surgery is severely underutilized, and concluded that lack of expertise, epilepsy centers, and funding contribute to this underutilization 9 …”
Section: Introductionmentioning
confidence: 99%